Properties of hybrid entanglement between discrete- and continuous-variable states of light. (29th June 2015) - Costanzo, L S; Zavatta, A; Grandi, S; Bellini, M; Jeong, H; Kang, M; Lee, S-W; Ralph, T C
Abstract: We discuss some of the main features of a recently-generated form of hybrid entanglement between discrete- and continuous-variable states of light. Ideally, such a kind of entanglement should involve single-photon and coherent states as key representatives of the respective categories of states. Here we investigate the characteristics and limits of a scheme that, relying on a superposition of photon-creation operators onto two distinct modes, realizes the above ideal form of hybrid entanglement in an approximate way.